Li4Ti5O12/hollow graphitized nano-carbon composites as anode materials for lithium ion battery. Issue 31 (11th March 2016) - Fan, Liping; Tan, Xin; Yu, Tao; Shi, Zhiqiang
Abstract : Li4 Ti5 O12 /hollow graphitized nano-carbon composites (LTO/HGCs) have been synthesized by a hydrothermal reaction using hollow graphitized nano-carbon as a conductive agent, and the composites were calcined at 750 °C for 12 h. Abstract : Li4 Ti5 O12 /hollow graphitized nano-carbon composites (LTO/HGCs) have been synthesized by a hydrothermal reaction using hollow graphitized nano-carbon as a conductive agent, and the composites were calcined at 750 °C for 12 h. The as-prepared particles are highly-crystalline spinel-type Li4 Ti5 O12 with a uniform particle size distribution, perfect crystal structure and small amounts of particle aggregation. The highly oriented hollow graphitized nano-carbon with a hexagonal carbon structure is uniformly distributed on the surface of Li4 Ti5 O12 nanoparticles, effectively improved the contact of Li4 Ti5 O12 nanoparticles. Electrochemical performance of the composites as anodes for lithium ion batteries is evaluated by galvanostatic discharge/charge, electrochemical impedance spectroscopy and cyclic voltammetry. The results show that the discharge capacity of composites with HGC (10.0 wt%) is 162.2 mA h g −1 and 105.4 mA h g −1 at the rate of 15 mA g −1 and 1.5 A g −1, respectively, and the discharge capacity retention rate after 500 cycles is 91.2% at 5C. The addition of hollow graphitized nano-carbon has improved the Li4 Ti5 O12 performance in terms of rate capacity, cycling life and capacity retention due to the improvement of electrical conductivity and decrease of resistance and polarization. These facts suggest that LTO/HGCs are one of the promising anode materials for high rate lithium ion batteries.